2014
DOI: 10.1002/pc.22973
|View full text |Cite
|
Sign up to set email alerts
|

Thermally stable electromagnetic interference shielding material from polysulfone nanocomposites: Comparison on carbon nanotube and nanofiber reinforcement

Abstract: The present investigation aims to develop thermally stable electromagnetic interference shielding materials from polysulfone (PSU) nanocomposites filled with multiwall carbon nanotubes (MWCNT) or carbon nanofibers (CNF). The effect of filler type and their structural features such as aspect ratio (length/diameter) and wall integrity on the different properties of nanocomposites has been investigated. Nanocomposite filled with MWCNT/CNF exhibits higher thermal stability compared with the neat PSU matrix. The on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The electrical percolation threshold of PI/CNT nanocomposites has been determined using the power law equation that can be given as follows . σαfalse(φφnormalcfalse)tforφ>φc …”
Section: Resultsmentioning
confidence: 99%
“…The electrical percolation threshold of PI/CNT nanocomposites has been determined using the power law equation that can be given as follows . σαfalse(φφnormalcfalse)tforφ>φc …”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8][9] Although metal-based shield materials have been used conventionally for a long time, carbon-filled polymer composites have attracted more interest in recent years due to many technical advantages in terms of density, cost, manufacturing and processing. In this context, polymer composites containing carbon nanofiber, [10,11] carbon nanotubes, [12,13] carbon black, [14] graphite, [15,16] and its different derivatives [17,18] have been extensively studied in the literature as EMI shielding materials.…”
Section: Introductionmentioning
confidence: 99%
“…Due to high conductivity and good dielectric and magnetic properties, carbon based materials such as graphite, expanded graphite and single or multiwalled CNTs have been widely used as EMI shields . Literature survey reveals that several studies have been reported on the EMI shielding properties of CNT and polymeric resins composites . Recently, Gupta et al .…”
Section: Introductionmentioning
confidence: 99%
“…Due to high conductivity and good dielectric and magnetic properties, carbon based materials such as graphite, expanded graphite and single or multiwalled CNTs have been widely used as EMI shields [34][35][36][37]. Literature survey reveals that several studies have been reported on the EMI shielding properties of CNT and polymeric resins composites [34,36,[38][39][40]. Recently, Gupta et al studied the EMI shielding properties of acid modified multiwalled CNTs (a-MWCNTs) reinforced PU composite films with 10 wt% of a-MWCNTs, where 229 dB shielding effectiveness was observed at thickness 1.5 mm with 10 wt% a-MWCNTs [36].…”
mentioning
confidence: 99%